Penerapan Media Pembelajaran Papercraft Dalam Meningkatkan Kreatifitas Menggambar Seni Budaya Dan Prakarya (SBDP) - Wina Maryuni, Ni Putu; Sari, Adi Purnama (Metta : Jurnal Ilmu Multidisiplin, 2023)
This research explores the application of papercraft as a learning medium to enhance creativity in drawing Cultural Arts and Crafts (SBDP). The study aims to assess the potential of papercraft in the context of SBDP education and its impact on students' creativity. The research methodology employed qualitative methods, specifically document analysis, to gather data on the implementation of papercraft in SBDP education. The findings indicate that papercraft serves as an effective tool for improving students' creative skills in SBDP. It facilitates the development of technical skills, fosters a deeper understanding of cultural arts, and encourages creative thinking. Moreover, papercraft has the potential to address challenges in SBDP education, such as resource limitations and student resistance. Furthermore, papercraft not only enhances learning but also motivates students, stimulates their imagination, and provides memorable learning experiences. With competent teacher support and seamless integration into the SBDP curriculum, papercraft can become a valuable addition to the field of cultural arts and crafts education. In conclusion, the application of papercraft in SBDP education represents a positive step toward enhancing students' creativity. Papercraft serves as a medium that allows students to tap into their creative potential and gain a deeper understanding of cultural arts. With proper implementation, papercraft has the potential to be an innovative and effective learning tool in SBDP education.